ANALISIS KEPERCAYAAN, CITRA MEREK DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPUASAN PELANGGAN (Studi Pada Kreditur PD. BKK Dempet Kota Kabupaten Demak) - ., Supriyadi; ., Marlien (Proceeding SENDI_U, 2015)
This study takes an object in PD. BKK Dempet Dempet City Branch Demak, where the reasons for selecting the titlebecause of the realization that achieved PD. BKK Dempet Dempet City Branch Demak 2009, 2012 and 2013 was notachieved so that it becomes a problem that must be addressed by the management of the bank. One way to boost therealization of loans obtained by the bank is to increase customer satisfaction and loyalty in lending transactions (credit)in the bank. Therefore, this study aims to identify and analyze the influence of trust, Brand Image and service quality onloyalty mediated by customer satisfaction (studies in PD. BKK Dempet Dempet City Branch Demak). Samples in thisstudy were 100 respondents who considered representative of the entire population. The sampling technique used in thisstudy purposive sampling is sampling based criteria or considerations such as: a customer of PD. BKK Dempet DempetCity Branch Demak for at least 2 years, and is domiciled in the territory Dempet, Demak. Tools of data analysis usingmultiple linear regression with mediation or intervening variables. The results show that there is a partial positive andsignificant effect of trust, confidence and quality of service to satisfaction. Partially there is a positive and significanteffect of trust, trust, quality of service and satisfaction to loyalty. The results show that the mediating effect ofsatisfaction does not mediate the effect of trust, brand image and service quality on customer loyalty.Keywords: trust, Brand image, service quality, satisfaction and loyalty.